KONTRIBUSI HAIL PERTANIAN PADI LADANG (MONDAU) TERHADAP KESEJAHTERAAN KELUARGA DI DESA WATMUMEREMBE KECAMATAN PALANGGA KABUPATEN KONAWE SELATAN - Asrianti, Asrianti; Sarmadan, Sarmadan; Jabar, Aryuni Salpiana (WELL-BEING: Journal of Social Welfare, 2022)
ThisÂ  research aims to determine and describe the contribution of rice farming in the (Mondau) field to the welfare of families in Watumerembe village Palangga district south Konawe Selatan. The method used is qualitative to carry out and describe the contribution of the results of rice farming in the ( Mondau ) field to the welfare of families in the village of Watumerembe palangga sub-district Konawe Selatan district based on the results of the study the results showed that: the contribution of the results pf the (Mondau) field rice family is a sense of security and happiness, the need for nutrition, education, health, housing, income.